Seroprevelance of Toxoplasma gondii (IgM,IgG) among Aborted Women in Some Karbala Hospital by using ELISA Technique and Microscopic Examination - Bahaa Alaa Farhan (Institute of Medico-legal Publications Pvt Ltd, 2020)
In this study, 100 pregnant women experiencing unnatural birth cycle go to the Karbala Maternity and Children Hospital from October/2018 to April/2019. These women submit to a history and physical examination . Blood tests from pregnant ladies were tried for IgG and IgM. Antibodies and suicide Mo graphic information’s were gathered. Their normal age was 29 years. The investigation demonstrated that enemy of Toxoplasma IgG, IgM, and by and large seropositivity of all antibodies were 42.85% and 57.14% separately. There was noteworthy impact of age on extent rate .The most noteworthy disease rates were found at 20-25 age gathering, while the least contamination rate found at 36-40 age gatherings. The all out predominance was more in Second Trimester of pregnancy (12.22%). IgG was increasingly amassed in Second Trimester (13.33%) than IgM (11.11%). No noteworthy distinction was found among residency and the commonness of Toxoplasma gondii antibodies in both rustic and urban territories. Watchwords: Toxoplasma gondii Infection, Toxoplasmosis. Using a microscopic sample of blood samples, 14 positive blood samples from 100 were found and the infection was identified by its characteristic characteristics .